Sciences sociales et lutte nationale dans les territoires occupés palestiniens - Vincent Romani (Revue d'anthropologie des connaissances)
The following article analyses the state and fate of social sciences in the Occupied Palestinian Territories. It explains how it is possible for social sciences to exist without a State, nor freedom, nor democracy. This study is based on a two-year-long field research focused on the Palestinian anthropologists, sociologists and political scientists of the West Bank and the Gaza Strip. It shows that coercion and national struggle, far from impeding the practice of science, nurture and frame it. Palestinian social scientists are thus pushed towards a fertile dependence towards international academic life. The study of social sciences allows to sketch a picture of the Palestinian society entering the violent post-Oslo era.